1966
DOI: 10.1677/joe.0.0350177
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence, Time, and Duration, of the Release of Follicle-Stimulating Hormone and Luteinizing Hormone in Relation to Oestrus and to Ovulation in the Sheep

Abstract: A difference in the timing of the release of follicle-stimulating hormone (FSH) and of luteinizing hormone (LH) from the pituitary of the sheep at about the time of the ovulatory discharge is described.The FSH content of the ovine pituitary began to decrease 8 hr. before the onset of oestrus, by which time 28 % of the FSH content of the pituitary had been discharged. The discharge of FSH continued at a steady rate until 6 hr. after the onset of oestrus to result in a further decrease of 24%.No change in the LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Estimates of LH secretion rate showed that a quantity equivalent to about half of pituitary LH content was apparently released after a single large dose of LHRH given in the luteal phase. The proportion was similar to that reported previously based on measurements of pituitary LH content in sheep killed at different times relative to ovulation (Robertson & Rakha 1966;Moss et al 1980). 1-4 + 0-5 3-O±O-6 7-2 + 3-2 12-5 ±2-8 8-7±4-9 5-5 ± 1-9 95-7 + 20-6(3) 374-5 ±75-7 (5) 352-7 + 53-0(3) 820-2+172-7(5) 233-5 ±92-3 (3) 346-7 ±30-2 (5) l-6±0-4 1-8 + 0-1 710 ± 15-9(3) 154-8 + 3-8 (6) 0-3 + 0-1 25-5 + 2-6(3) 0-7 ±0-3 25-4 + 4-7 (6) 8-5+1-8 13-2 + 3-0 8-4±l-6 8-2 + 3-0 299-7 ±73-4 (3) 554-2 + 39-9(6) 325-5 ± 40-4 (3) 395-9+123-0(4) 3-5+1-3 7-8 ±3-4 12-2 ±5-6 35-0 ±10-5 101-0+16-4(3) 283-8 + 83-2(6) 446-l±90-3(3) 1470-2 + 484-0(4)…”
Section: Pituitary Secretion Ratessupporting
confidence: 89%
“…Estimates of LH secretion rate showed that a quantity equivalent to about half of pituitary LH content was apparently released after a single large dose of LHRH given in the luteal phase. The proportion was similar to that reported previously based on measurements of pituitary LH content in sheep killed at different times relative to ovulation (Robertson & Rakha 1966;Moss et al 1980). 1-4 + 0-5 3-O±O-6 7-2 + 3-2 12-5 ±2-8 8-7±4-9 5-5 ± 1-9 95-7 + 20-6(3) 374-5 ±75-7 (5) 352-7 + 53-0(3) 820-2+172-7(5) 233-5 ±92-3 (3) 346-7 ±30-2 (5) l-6±0-4 1-8 + 0-1 710 ± 15-9(3) 154-8 + 3-8 (6) 0-3 + 0-1 25-5 + 2-6(3) 0-7 ±0-3 25-4 + 4-7 (6) 8-5+1-8 13-2 + 3-0 8-4±l-6 8-2 + 3-0 299-7 ±73-4 (3) 554-2 + 39-9(6) 325-5 ± 40-4 (3) 395-9+123-0(4) 3-5+1-3 7-8 ±3-4 12-2 ±5-6 35-0 ±10-5 101-0+16-4(3) 283-8 + 83-2(6) 446-l±90-3(3) 1470-2 + 484-0(4)…”
Section: Pituitary Secretion Ratessupporting
confidence: 89%
“…It is believed that this has resulted in a better estimate of the time-relationship between oestrogen production and the onset of oestrus. Robertson & Rakha (1966) have shown that pituitary FSH is not released until about 8 h before the onset of oestrus. Hence the occurrence of the peak of oestrogen concentration and production at the onset of oestrus, rather than earlier, is more compatible with the concept that FSH is involved in the production of oestrogen.…”
Section: Chemical Analysismentioning
confidence: 99%
“…The observations of increased thyroid activity in the ewe at oestrus were not as precise with respect to the time of onset of oestrus as were the studies of Robertson & Rakha (1966), but close examination indicated several examples of acceleration of thyroid activity at or near the onset of oestrus (Falconer, 1960;Robertson & Falconer, 1961 b). It would therefore appear that the activation of the thyroid during oestrus is approximately coincident with the period of rapid release of gonadotrophins and of high oestrogen concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…The lowest pituitary FSH content occurred at 6 hr after the onset of oestrus, which also coincided with the lowest pituitary LH content. The release of LH occurred over a much shorter time than of FSH, between 0 and 6 hr after the onset of oestrus (Robertson & Rakha, 1966).…”
Section: Resultsmentioning
confidence: 96%